AST/ALT Ratio and Peripheral Artery Disease in a Chinese Hypertensive Population: A Cross-Sectional Study. (November 2021) - Liu, Hui; Zha, Xiaoyuan; Ding, Congcong; Hu, Lihua; Li, Minghui; Yu, Yu; Zhou, Wei; Wang, Tao; Zhu, Lingjuan; Bao, Huihui; Cheng, Xiaoshu
Previous studies reported that the aspartate aminotransferase (AST) to alanine aminotransferase (ALT) ratio (AST/ALT) was a risk factor in cardiovascular disease. Peripheral artery disease (PAD) is an important risk factor for cardiovascular death. However, only a few studies investigated the correlations between the AST/ALT ratio and PAD. We analyzed data from 10 900 patients with hypertension from the Chinese Hypertension Registry Study; 350 patients had PAD (prevalence 3.2%). After adjusting for potential confounders, the AST/ALT ratio was independently and positively associated with risk of PAD (OR: 1.31, 95% CI, 1.13-1.59), and a significant increased risk of PAD for the third AST/ALT ratio tertile (T3) compared with the first tertile (T1; OR: 1.49, 95% CI, 1.09-2.04, P trend = .005) was found. Moreover, when we combined T1 and T2 into one group and used it as a reference group, the risk of PAD increased with the increase in AST/ALT; the risk ratio was 1.52 (95% CI, 1.20-1.95). A higher AST/ALT ratio (≥1.65) was associated with PAD risk in Chinese adults with hypertension. Our results suggest that the AST/ALT ratio may help identify patients at high risk of vascular end points and might be a convenient, economical, and effective tool for evaluating the risk of atherosclerosis.